Motions of the Convection Reversal Boundary and Local Plasma in the High‐Latitude Ionosphere. Issue 4 (6th April 2018) - Chen, Yun‐Ju; Heelis, Roderick A.
Abstract: We present results from a systematic study of multisatellite samplings from the Defense Meteorological Satellite Program F13, F15, F16, F17, and F18 satellites over the period from 2007 to 2015 that describe the motion of the convection reversal boundary (CRB) and the local plasma flow across it. Focusing on the cases with continuous poleward and equatorward CRB motion sampled by three consecutive satellites within 50 min, 45% of the time the CRB motion may deviate from the local plasma motion near dawn and dusk where the reconnection process is unlikely to be present. Differences in the inferred CRB motion and the local plasma motion may arise from apparent motion induced by the local time displacement of consecutive samples across the CRB that is tilted with respect to a line of constant latitude. The presence of a viscous‐like interaction across the CRB can also contribute to the difference in the CRB and plasma motion. Accounting for these processes, the CRB motion and the motion of the plasma at the CRB are consistent only if a back and forth motion over a timescale of a few minutes is superimposed on a monotonic migration of the CRB over longer time periods. Key Points: Plasma and CRB motion are consistent with adiaroic behavior if jitter motion over a few minutes is superimposed on a monotonic CRB motion Viscous‐like interaction may contribute to the differences in plasma and CRB motion at an adiaroic boundary